Establishing the international research priorities for pediatric emergency medicine point‐of‐care ultrasound: A modified Delphi study. (13th September 2022) - Snelling, Peter J.; Shefrin, Allan E.; Moake, Matthew M.; Bergmann, Kelly R.; Constantine, Erika; Deanehan, J. Kate; Dessie, Almaz S.; Elkhunovich, Marsha A.; Gold, Delia L.; Kornblith, Aaron E.; Lin‐Martore, Margaret; Nti, Benjamin; et al.
Abstract: Background: The Pediatric Emergency Medicine (PEM) Point‐of‐care Ultrasound (POCUS) Network (P2Network) was established in 2014 to provide a platform for international collaboration among experts, including multicenter research. The objective of this study was to use expert consensus to identify and prioritize PEM POCUS topics, to inform future collaborative multicenter research. Methods: Online surveys were administered in a two‐stage, modified Delphi study. A steering committee of 16 PEM POCUS experts was identified within the P2Network, with representation from the United States, Canada, Italy, and Australia. We solicited the participation of international PEM POCUS experts through professional society mailing lists, research networks, social media, and "word of mouth." After each round, responses were refined by the steering committee before being reissued to participants to determine the ranking of all the research questions based on means and to identify the high‐level consensus topics. The final stage was a modified Hanlon process of prioritization round (HPP), which emphasized relevance, impact, and feasibility. Results: Fifty‐four eligible participants (16.6%) provided 191 items to Survey 1 (Round 1). These were refined and consolidated into 52 research questions by the steering committee. These were issued for rating in Survey 2 (Round 2), which had 45 participants. At the completion of Round 2, all questions were ranked with six research questions reaching high‐level consensus. Thirty‐one research questions with mean ratings above neutral were selected for the HPP round. Highly ranked topics included clinical applications of POCUS to evaluate and manage children with shock, cardiac arrest, thoracoabdominal trauma, suspected cardiac failure, atraumatic limp, and intussusception. Conclusions: This consensus study has established a research agenda to inform future international multicenter PEM POCUS trials. This study has highlighted the ongoing need for high‐quality evidence for PEM POCUS applications to guide clinical practice.